prev next
File: TortureTests/Size/100.html
Author: Robert Miner
Description: Mid-sized stress test containing 100 separate equations.
Sample Rendering: N/A

Your browser's rendering:

x 0 + 0 = α x 1 + 1 = β x 2 + 2 = γ x 3 + 3 = δ x 4 + 4 = α x 5 + 5 = β x 6 + 6 = γ x 7 + 7 = δ x 8 + 8 = α x 9 + 9 = β x 10 + 10 = γ x 11 + 11 = δ x 12 + 12 = α x 13 + 13 = β x 14 + 14 = γ x 15 + 15 = δ x 16 + 16 = α x 17 + 17 = β x 18 + 18 = γ x 19 + 19 = δ x 20 + 20 = α x 21 + 21 = β x 22 + 22 = γ x 23 + 23 = δ x 24 + 24 = α x 25 + 25 = β x 26 + 26 = γ x 27 + 27 = δ x 28 + 28 = α x 29 + 29 = β x 30 + 30 = γ x 31 + 31 = δ x 32 + 32 = α x 33 + 33 = β x 34 + 34 = γ x 35 + 35 = δ x 36 + 36 = α x 37 + 37 = β x 38 + 38 = γ x 39 + 39 = δ x 40 + 40 = α x 41 + 41 = β x 42 + 42 = γ x 43 + 43 = δ x 44 + 44 = α x 45 + 45 = β x 46 + 46 = γ x 47 + 47 = δ x 48 + 48 = α x 49 + 49 = β x 50 + 50 = γ x 51 + 51 = δ x 52 + 52 = α x 53 + 53 = β x 54 + 54 = γ x 55 + 55 = δ x 56 + 56 = α x 57 + 57 = β x 58 + 58 = γ x 59 + 59 = δ x 60 + 60 = α x 61 + 61 = β x 62 + 62 = γ x 63 + 63 = δ x 64 + 64 = α x 65 + 65 = β x 66 + 66 = γ x 67 + 67 = δ x 68 + 68 = α x 69 + 69 = β x 70 + 70 = γ x 71 + 71 = δ x 72 + 72 = α x 73 + 73 = β x 74 + 74 = γ x 75 + 75 = δ x 76 + 76 = α x 77 + 77 = β x 78 + 78 = γ x 79 + 79 = δ x 80 + 80 = α x 81 + 81 = β x 82 + 82 = γ x 83 + 83 = δ x 84 + 84 = α x 85 + 85 = β x 86 + 86 = γ x 87 + 87 = δ x 88 + 88 = α x 89 + 89 = β x 90 + 90 = γ x 91 + 91 = δ x 92 + 92 = α x 93 + 93 = β x 94 + 94 = γ x 95 + 95 = δ x 96 + 96 = α x 97 + 97 = β x 98 + 98 = γ x 99 + 99 = δ x 100 + 100 = α


Source Code:

    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>0</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>0</mn> 
      <mo>=</mo> 
      <mi>&alpha;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>1</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>1</mn> 
      <mo>=</mo> 
      <mi>&beta;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>2</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>2</mn> 
      <mo>=</mo> 
      <mi>&gamma;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>3</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>3</mn> 
      <mo>=</mo> 
      <mi>&delta;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>4</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>4</mn> 
      <mo>=</mo> 
      <mi>&alpha;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>5</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>5</mn> 
      <mo>=</mo> 
      <mi>&beta;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>6</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>6</mn> 
      <mo>=</mo> 
      <mi>&gamma;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>7</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>7</mn> 
      <mo>=</mo> 
      <mi>&delta;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>8</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>8</mn> 
      <mo>=</mo> 
      <mi>&alpha;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>9</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>9</mn> 
      <mo>=</mo> 
      <mi>&beta;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>10</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>10</mn> 
      <mo>=</mo> 
      <mi>&gamma;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>11</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>11</mn> 
      <mo>=</mo> 
      <mi>&delta;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>12</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>12</mn> 
      <mo>=</mo> 
      <mi>&alpha;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>13</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>13</mn> 
      <mo>=</mo> 
      <mi>&beta;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>14</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>14</mn> 
      <mo>=</mo> 
      <mi>&gamma;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>15</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>15</mn> 
      <mo>=</mo> 
      <mi>&delta;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>16</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>16</mn> 
      <mo>=</mo> 
      <mi>&alpha;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>17</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>17</mn> 
      <mo>=</mo> 
      <mi>&beta;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>18</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>18</mn> 
      <mo>=</mo> 
      <mi>&gamma;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>19</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>19</mn> 
      <mo>=</mo> 
      <mi>&delta;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>20</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>20</mn> 
      <mo>=</mo> 
      <mi>&alpha;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>21</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>21</mn> 
      <mo>=</mo> 
      <mi>&beta;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>22</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>22</mn> 
      <mo>=</mo> 
      <mi>&gamma;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>23</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>23</mn> 
      <mo>=</mo> 
      <mi>&delta;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>24</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>24</mn> 
      <mo>=</mo> 
      <mi>&alpha;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>25</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>25</mn> 
      <mo>=</mo> 
      <mi>&beta;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>26</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>26</mn> 
      <mo>=</mo> 
      <mi>&gamma;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>27</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>27</mn> 
      <mo>=</mo> 
      <mi>&delta;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>28</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>28</mn> 
      <mo>=</mo> 
      <mi>&alpha;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>29</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>29</mn> 
      <mo>=</mo> 
      <mi>&beta;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>30</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>30</mn> 
      <mo>=</mo> 
      <mi>&gamma;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>31</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>31</mn> 
      <mo>=</mo> 
      <mi>&delta;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>32</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>32</mn> 
      <mo>=</mo> 
      <mi>&alpha;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>33</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>33</mn> 
      <mo>=</mo> 
      <mi>&beta;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>34</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>34</mn> 
      <mo>=</mo> 
      <mi>&gamma;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>35</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>35</mn> 
      <mo>=</mo> 
      <mi>&delta;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>36</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>36</mn> 
      <mo>=</mo> 
      <mi>&alpha;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>37</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>37</mn> 
      <mo>=</mo> 
      <mi>&beta;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>38</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>38</mn> 
      <mo>=</mo> 
      <mi>&gamma;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>39</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>39</mn> 
      <mo>=</mo> 
      <mi>&delta;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>40</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>40</mn> 
      <mo>=</mo> 
      <mi>&alpha;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>41</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>41</mn> 
      <mo>=</mo> 
      <mi>&beta;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>42</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>42</mn> 
      <mo>=</mo> 
      <mi>&gamma;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>43</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>43</mn> 
      <mo>=</mo> 
      <mi>&delta;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>44</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>44</mn> 
      <mo>=</mo> 
      <mi>&alpha;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>45</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>45</mn> 
      <mo>=</mo> 
      <mi>&beta;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>46</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>46</mn> 
      <mo>=</mo> 
      <mi>&gamma;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>47</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>47</mn> 
      <mo>=</mo> 
      <mi>&delta;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>48</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>48</mn> 
      <mo>=</mo> 
      <mi>&alpha;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>49</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>49</mn> 
      <mo>=</mo> 
      <mi>&beta;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>50</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>50</mn> 
      <mo>=</mo> 
      <mi>&gamma;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>51</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>51</mn> 
      <mo>=</mo> 
      <mi>&delta;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>52</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>52</mn> 
      <mo>=</mo> 
      <mi>&alpha;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>53</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>53</mn> 
      <mo>=</mo> 
      <mi>&beta;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>54</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>54</mn> 
      <mo>=</mo> 
      <mi>&gamma;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>55</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>55</mn> 
      <mo>=</mo> 
      <mi>&delta;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>56</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>56</mn> 
      <mo>=</mo> 
      <mi>&alpha;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>57</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>57</mn> 
      <mo>=</mo> 
      <mi>&beta;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>58</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>58</mn> 
      <mo>=</mo> 
      <mi>&gamma;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>59</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>59</mn> 
      <mo>=</mo> 
      <mi>&delta;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>60</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>60</mn> 
      <mo>=</mo> 
      <mi>&alpha;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>61</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>61</mn> 
      <mo>=</mo> 
      <mi>&beta;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>62</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>62</mn> 
      <mo>=</mo> 
      <mi>&gamma;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>63</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>63</mn> 
      <mo>=</mo> 
      <mi>&delta;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>64</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>64</mn> 
      <mo>=</mo> 
      <mi>&alpha;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>65</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>65</mn> 
      <mo>=</mo> 
      <mi>&beta;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>66</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>66</mn> 
      <mo>=</mo> 
      <mi>&gamma;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>67</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>67</mn> 
      <mo>=</mo> 
      <mi>&delta;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>68</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>68</mn> 
      <mo>=</mo> 
      <mi>&alpha;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>69</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>69</mn> 
      <mo>=</mo> 
      <mi>&beta;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>70</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>70</mn> 
      <mo>=</mo> 
      <mi>&gamma;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>71</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>71</mn> 
      <mo>=</mo> 
      <mi>&delta;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>72</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>72</mn> 
      <mo>=</mo> 
      <mi>&alpha;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>73</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>73</mn> 
      <mo>=</mo> 
      <mi>&beta;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>74</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>74</mn> 
      <mo>=</mo> 
      <mi>&gamma;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>75</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>75</mn> 
      <mo>=</mo> 
      <mi>&delta;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>76</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>76</mn> 
      <mo>=</mo> 
      <mi>&alpha;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>77</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>77</mn> 
      <mo>=</mo> 
      <mi>&beta;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>78</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>78</mn> 
      <mo>=</mo> 
      <mi>&gamma;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>79</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>79</mn> 
      <mo>=</mo> 
      <mi>&delta;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>80</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>80</mn> 
      <mo>=</mo> 
      <mi>&alpha;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>81</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>81</mn> 
      <mo>=</mo> 
      <mi>&beta;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>82</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>82</mn> 
      <mo>=</mo> 
      <mi>&gamma;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>83</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>83</mn> 
      <mo>=</mo> 
      <mi>&delta;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>84</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>84</mn> 
      <mo>=</mo> 
      <mi>&alpha;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>85</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>85</mn> 
      <mo>=</mo> 
      <mi>&beta;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>86</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>86</mn> 
      <mo>=</mo> 
      <mi>&gamma;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>87</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>87</mn> 
      <mo>=</mo> 
      <mi>&delta;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>88</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>88</mn> 
      <mo>=</mo> 
      <mi>&alpha;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>89</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>89</mn> 
      <mo>=</mo> 
      <mi>&beta;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>90</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>90</mn> 
      <mo>=</mo> 
      <mi>&gamma;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>91</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>91</mn> 
      <mo>=</mo> 
      <mi>&delta;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>92</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>92</mn> 
      <mo>=</mo> 
      <mi>&alpha;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>93</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>93</mn> 
      <mo>=</mo> 
      <mi>&beta;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>94</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>94</mn> 
      <mo>=</mo> 
      <mi>&gamma;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>95</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>95</mn> 
      <mo>=</mo> 
      <mi>&delta;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>96</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>96</mn> 
      <mo>=</mo> 
      <mi>&alpha;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>97</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>97</mn> 
      <mo>=</mo> 
      <mi>&beta;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>98</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>98</mn> 
      <mo>=</mo> 
      <mi>&gamma;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>99</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>99</mn> 
      <mo>=</mo> 
      <mi>&delta;</mi> 
    </math> 
    <span>. Consider the equation</span> 
    <math> 
      <msup> 
        <mi>x</mi> 
        <mn>100</mn> 
      </msup> 
      <mo>+</mo> 
      <mn>100</mn> 
      <mo>=</mo> 
      <mi>&alpha;</mi> 
    </math> 
    <span>.</span>
  

Test Suite Home